2020
DOI: 10.34172/hpp.2020.35
|View full text |Cite
|
Sign up to set email alerts
|

Fear of negative appearance evaluation and attitude towards mammography: Moderating role of internal health locus of control,cancer worry and age

Abstract: Background: Mammography screening tends to reduce mortality rate through early detection. One of the barriers to mammography screening is fear of negative appearance evaluation(FNAE). This study investigated the impact of internal health locus of control, breast cancer worries and age on the relationship between FNAE and attitude towards mammography. Methods: A cross-sectional, questionnaire-based survey design was used. Samples were Iranian women, living in Iran, aged at least 30 years old, without any histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…According to a study by Xia and Ma [ 23 ], having an IHLC enhances mental health and health-related behavior by reducing the intensity of stress. Additionally, a study by Sharif et al [ 22 ] on women with diseases suggested that to overcome diseases and actively treat them, a change from PHLC to IHLC should be made. Moreover, Steptoe and Wardle [ 50 ] found that students with a strong IHLC are more likely to exercise, eat breakfast regularly, brush their teeth daily, eat fiber, limit their salt intake, and avoid eating fatty foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study by Xia and Ma [ 23 ], having an IHLC enhances mental health and health-related behavior by reducing the intensity of stress. Additionally, a study by Sharif et al [ 22 ] on women with diseases suggested that to overcome diseases and actively treat them, a change from PHLC to IHLC should be made. Moreover, Steptoe and Wardle [ 50 ] found that students with a strong IHLC are more likely to exercise, eat breakfast regularly, brush their teeth daily, eat fiber, limit their salt intake, and avoid eating fatty foods.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have failed to examine the relationship among all variables comprehensively. In addition, most studies have focused on patients with diseases [ 21 , 22 ], adults [ 23 , 24 ], and college students [ 18 , 25 ], while there is a lack of studies on adolescents, who are in a critical period of learning and growth.…”
Section: Introductionmentioning
confidence: 99%
“…According to this finding, as the locus of control of the student's decreases, social appearance anxiety increases. Pahlevan Sharif et al (2020) concluded that locus of control is associated with negative appearance evaluation. Based on these results, it can be said that individuals with an internal locus of control experience less social appearance anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to support women in making personalized, informed decisions regarding managing and controlling their menopausal symptoms [6,8,9]. When women believe they have control over their health, they are more likely to engage in healthy behaviors such as a balanced diet and physical activity [10,11]. In fact, the perception of Health Locus of Control (HLC) among menopausal women is crucial in promoting healthy behaviors and effectively managing menopausal symptoms [10,12].…”
Section: Introductionmentioning
confidence: 99%